Coexistence of Fibromyalgia, Myofascial Pain Syndrome and Depression Among Patients with Lumbar Disc Herniation - Gonca Saglam; Serdar Karakullukcu; Hanife Baykal Sahin; Demet Saglam Aykut (Haseki Tıp Bülteni, 2022)

(untitled)
Aim:Pain in lumbar disc herniation (LDH) may originate from a multisource other than the intervertebral disc, and magnetic resonance imaging (MRI) findings are not always correlated with clinical symptoms in LDH patients. This study aimed to determine the prevalence of fibromyalgia (FM), myofascial pain syndrome (MPS), and depression in patients with LDH and to evaluate the clinical variations caused by these comorbidities.Methods:One hundred and fifty-four patients with a diagnosis of LDH confirmed by MRI and admitted to a physical medicine and rehabilitation outpatient clinic between July 2021 and January 2022 were enrolled in this cross-sectional study. Pain intensity was recorded according to the visual analog scale (VAS). The presence of FM and MPS was examined. The Beck Depression Inventory (BDI) was used to research the presence of depression. Patients were divided into three groups: LDH without FM or MPS, LDH+FM, LDH+MPS.Results:Of the 154 LDH patients, 60 of them had LDH without FM or MPS (38.9%), 52 of them had LDH+FM (33.8%), and 42 of them had LDH+MPS (27.3%). Forty-eight LDH patients (31.2%) had depression. The mean VAS of the FM+LDH group was higher than that of the other two groups (p<0.001). Depression was more common in the LDH+FM and LDH+MPS groups than in the LDH without the FM or MPS group (p<0.001).Conclusion:These results indicate that the coexistence of FM, MPS, and depression in LDH patients is frequent, and a multidimensional approach is required for LDH treatment.